A 2015 social accounting Matrix (SAM) for Mozambique - António Cruz; Fausto Mafambissa; Mónica Magáua; Vincenzo Salvucci; Dirk Ernst van Seventer (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2018)
This paper documents a 2015 Social Accounting Matrix (SAM) for Mozambique. The SAM is built using unpublished Instituto Nacional de Estatística (INE) industry-level production accounts, commodity-level supply-demand balances and a supply matrix, together with national accounts, National Directorate of Planning and Budget (DNPO) government statistics and IMF balance of payment statistics (all for the year 2015), INE household and labour market survey data for 2014-15 and a use matrix from a 2007 SAM for Mozambique. It provides a detailed representation of the Mozambican economy and identifies 55 activities and commodities. Labour is disaggregated by education attainment level and household income and expenditure by per capita expenditure quintiles both for urban and rural areas. The SAM features production for home consumption as reported in the unpublished INE accounts and the INE household survey data and also presents government, investment, and foreign accounts. The SAM is a useful database for conducting economy-wide impact assessments, including multiplier analysis and computable general equilibrium (CGE) modelling.
Keywords: C63; E01; E16; P44; 330; Social accounting matrix; national accounts; supply table; use table; cross-entropy SAM estimation